Differences in Body Hydration Before and After the Judo Training of Young Athletes - Amel Mekic; Faris Rasidagic; Izet Bajramovic; Slavenko Likic; Merima Merdan (Journal of Anthropology of Sport and Physical Education, 2019)
The aim of the research is to determine the diff erence between hydration of the body before and after the judo training. The sample of respondents was boys (N = 30) aged 11-12 years. Body mass (MASS), body mass index (BMI), body fat (FET) and body water (BTW) were measured. The mean values in the second measurement were lower: body weight by 0.6 kg, body mass index by 0.5, body weight for 0.2 kg and body water by 0.8 kg. The trend of decreasing the minimum and maximum values is also noticeable in all treated variables except in the case of maximum values of body fat variables. Statistical signifi cance was confi rmed by t-test at p<0.05 in case of body mass index and body weight index, and p<0.01 in case of body water variable. The body fat change was not statistically signifi cant. After the conducted study, it can be concluded that there is a justifi ed need for rehydration during training. In order to maintain the appropriate training intensity, judo coaches should plan organized breaks. Coaches or other trainers of physical activities with the contents of the judo sport are recommended to provide organized breaks during which the course will be rejuvenated.